KAJIAN DAN OPINI MAHASISWA TERHADAP PENGGUNAAN APLIKASI TEACHMINT PADA MATAKULIAH LOGIKA MATEMATIKA - Rahmawati Yuliyani; Sri Rezeki; Bayu Jaya Tama (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) AMIK Indonesia, 2023)
The Teachmint application is an all in one learning application based in India and has started to develop everywhere, one of them is in Indonesia, as well as the languages used are also available in various languages including Indonesian. This application is quite complete in its use, namely there is a live video session facility that allows direct interaction between lecturers and students, there is a blackboard that is not limited to the number of pages as if students are studying offline and is immediately saved automatically both in pdf and video form recording. The drawbacks of this application can almost be said to be non-existent, apart from the need for a stable internet network and quota to be fulfilled like other video call applications so if all of these are not fulfilled then of course this application will not be optimal. This study discusses the views or opinions of students as users during mathematical logic lectures. Based on the results of questionnaires and interviews conducted, it was found that this application is good for online learning because it can store all lecture materials together so that they are not scattered and all are fully documented, both in the pdf version and the video version as a result of the automatic recording during the live session.